Intrinsic nanostructure induced ultralow thermal conductivity yields enhanced thermoelectric performance in Zintl phase Eu2ZnSb2 - Chen Chen (Nature Portfolio, 2021)
Understanding mechanisms for obtaining low thermal conductivity without degraded electrical properties remains a challenge. Here, the authors reveal a mechanism for thermal conductivity reduction in a Zintl phase thermoelectric based on length scales for disorder in Eu2ZnSb2.